Enjeux individuels et institutionnels au cœur d'un dispositif innovant : le doctorat par la validation des acquis de l'expérience dans le champ de l'architecture - Pascal Lafont; Marcel Pariat; Zohra Bacha
The Social Modernization Act of 2002 introduces a new certification path since anyone, engaged in active life for at least one year, can have their experience validated in order to obtain a degree or title with a professional purpose. Also, the pattern in which a certification was the final sanction of an academic or professional training is modified. How, in the case of the doctorate, could VAE appear as an innovation with changes in the way of awarding the title of doctor? The hypothesis proposed is that the intentionalities of the actors would be indicative of individual and institutional issues in the field of research. It is thus a question of analyzing the application of the VAE at the doctoral level according to the institutional requirements likely to carry an innovative device in emergence. Methodologically, the corpus consists of semi-structured interviews of doctoral school directors (ED), minutes of steering committee meetings, and a meeting with the representatives of the laboratories sitting on the board of directors. doctoral school (ED) of the specialty "architecture". Borrowing from action research and participant observation is evident, and discourse analysis leads to the identification of representations made by the actors of the VAE doctoral program. Finally, it is a case study of the relationships that innovation and change maintain, a conflictual relationship when the resistance to change is considered as a brake on the dynamics of innovation, strategic relationship and sometimes hidden when the innovation serves a promoted change.